Factors Effecting Phone Brand’s Purchase Decision, Mediated By Purchase Intention - Suprapto, Yandi; Halim, Wiliana; Kesumahati, Eriliana (Islamic University of Kalimantan MAB Banjarmasin, 2026)
As the global market continues to change dynamically, smartphone brands industry constantly developing and innoovate new features to fulfill the market demands. The rising of new demands feature resulting businesses to have to intensify their efforts to address those needs, while still maintaining continues rise of sales to earn revenues. This research was done with the intention to study further the role of purchase intention mediating the relationships between social media marketing, brand image, E-WOM, and purchase decision as the dependent. By using quantitive method to obtain the data for this research, a sum of 253 different respondents was gathered all over Indonesia with the type of sampling used was nonprobability. The data gathered were then proceesed by using Smart PLS 3 and SPSS 27. This research resulted that all hypothesis is accepted, except for those who’re involved with the social media marketing variable are rejected. In essence, these findings indicate that businesses can utilize better aspects such as brand image and EWOM in gaining customers willingness to purhcase their products.